2005
DOI: 10.1002/hlca.200590199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New C(2)‐Substituted gluco‐Configured Tetrahydroimidazopyridines and Their Evaluation as Glucosidase Inhibitors

Abstract: Albert Eschenmoser zum 80. Geburtstag mit herzlichen Glückwünschen zugeeignet.The gluco-configured C(2)-substituted tetrahydroimidazopyridines 8 -14 were prepared and tested as inhibitors of the b-glucosidases from Caldocellum saccharolyticum and from sweet almonds, and of the a-glucosidase from brewer's yeast. All new imidazopyridines are nanomolar inhibitors of the b-glucosidases and micromolar inhibitors of the a-glucosidase. The 3-phenylpropyl derivative 14 proved the strongest inhibitor of the Caldocellum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…3 . These compounds have been synthesised to mimic different glycosides, 121-124 with a number of different functional groups attached to mimic the aglycon, 125-129 and in oligosaccharide forms. 117 It is interesting to note that if a triazole moiety is fused to the pseudo-glycoside ring ( i.e.…”
Section: Glycosidase Inhibitorsmentioning
confidence: 99%
“…3 . These compounds have been synthesised to mimic different glycosides, 121-124 with a number of different functional groups attached to mimic the aglycon, 125-129 and in oligosaccharide forms. 117 It is interesting to note that if a triazole moiety is fused to the pseudo-glycoside ring ( i.e.…”
Section: Glycosidase Inhibitorsmentioning
confidence: 99%
“…Following its discovery, nagstatin was synthesized [132] and the scaffold manipulated to make potent β-glucosidase inhibitors [133, 134]. These tetrahydroimidazopyridine compounds were substituted with a number of different functional groups in order to promote favourable interactions in the active site of enzymes of interest [135-138], and these have proven to be among the most potent β-glycosidase inhibitors studied [139]. The potency of the tetrahydroimidazopyridine compounds are attributed to the protonated nitrogen atom in the imidazole forming a strong hydrogen bond interaction with the general acid/base residue, and the pseudo-glycoside ring adopting a half chair/envelope conformation which mimics the proposed oxocarbenium transition state [140].…”
Section: Inhibition Of Ogamentioning
confidence: 99%
“…Furthermore, critical evaluation of the nature of the C2 substituent showed that an aglyconmimicking group in this position results in stronger inhibition. 19,20 Combining the current body of knowledge on the glycoimidazoles together with the structural data of the bOGA-PUGNAc complex, we designed a series of GlcNAc-configured nagstatin derivatives (GlcNAcstatins) that address specificity toward the OGA enzymes through elaborated N8 (tetrahydroimidazopyridine numbering) acyl derivatives while providing a source of increased affinity through the incorporation of suitable C2 substituents. Here we report the synthesis of GlcNAcstatin (1, Figure 1), a glucoimidazole with molecular architecture noticeably similar to that of PUGNAc, but bearing a larger isobutanamido group on N8 and a phenethyl group on C2.…”
mentioning
confidence: 99%
“…In 1995 Tatsuta reported the total synthesis of this compound and a series of related glycoimidazole derivatives with variable configuration of the sugar ring, showing up to nanomolar inhibition against a panel of glycosidases. , Subsequent work by the Vasella group defined the structure−activity relationships of nagstatin analogues (tetrahydroimidazo[1,2- a ]pyridines) as glycosidase inhibitors, making use of an original synthetic approach to the bicyclic core structure, showing that the molecular architecture of these compounds in the ground state accurately mimics the assumed flattened half-chair/envelope conformation of the sugar ring in the transition state, while protonation of the imidazole ring effectively emulates the charge distribution in the oxocarbenium ion. Furthermore, critical evaluation of the nature of the C2 substituent showed that an aglycon-mimicking group in this position results in stronger inhibition. , Combining the current body of knowledge on the glycoimidazoles together with the structural data of the bOGA−PUGNAc complex, we designed a series of GlcNAc-configured nagstatin derivatives (GlcNAcstatins) that address specificity toward the OGA enzymes through elaborated N8 (tetrahydroimidazopyridine numbering) acyl derivatives while providing a source of increased affinity through the incorporation of suitable C2 substituents. Here we report the synthesis of GlcNAcstatin ( 1 , Figure ), a glucoimidazole with molecular architecture noticeably similar to that of PUGNAc, but bearing a larger isobutanamido group on N8 and a phenethyl group on C2.…”
mentioning
confidence: 99%